2000
DOI: 10.1074/jbc.275.17.12799
|View full text |Cite
|
Sign up to set email alerts
|

α1-Proteinase Inhibitor, α1-Antichymotrypsin, or α2-Macroglobulin Is Required for Vascular Smooth Muscle Cell Spreading in Three-dimensional Fibrin Gel

Abstract: It is assumed that vitronectin and other adhesion molecules induce cell spreading. We found that vascular smooth muscle cells require unidentified plasma components besides adhesion molecules to spread in fibrin gel, a likely provisional matrix at wound sites. By purification, the plasma components were found to be ␣ 1 -proteinase inhibitor, ␣ 1 -antichymotrypsin, and ␣ 2 -macroglobulin. The chemically inactivated ␣ 1 -proteinase inhibitor and ␣ 2 -macroglobulin lose the spreading activity, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…It has already been demonstrated that PMNs could induce detachment of endothelial cells from the extracellular matrix, 55,56 as they do for smooth muscle cells. 23 It has been recently shown that serum-derived serine proteinase inhibitors are necessary for the spreading of SMCs on a fibrin gel 57 and prevented both fibronectin degradation and SMC apoptosis subsequent to the loss of anchorage. 58 However, as pericellular proteolysis is a necessary condition for cell migration, serine proteases with elastase activity could be also involved in SMC migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated that PMNs could induce detachment of endothelial cells from the extracellular matrix, 55,56 as they do for smooth muscle cells. 23 It has been recently shown that serum-derived serine proteinase inhibitors are necessary for the spreading of SMCs on a fibrin gel 57 and prevented both fibronectin degradation and SMC apoptosis subsequent to the loss of anchorage. 58 However, as pericellular proteolysis is a necessary condition for cell migration, serine proteases with elastase activity could be also involved in SMC migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…49 A failure of vascular SMCs to repair wounds adequately may play a part in plaque rupture and sudden death. Yee and Schwartz 49 found that fibronectin present in the clot links fibrin and SMCs, and they demonstrated that plasma protease inhibitors are required to prevent degradation of fibronectin (Ikari et al 50 ). An inhibition of fibronectin binding to fibrin by homocysteine may lead to a deficiency of fibronectin in the clot.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronate is one of the ECM glycosaminoglycans; it can form gels by covalently crosslinking with various hydrazide derivatives, and be degraded by hyaluronidase (Pouyani et al, 1994, Vercruysse et al, 1997. Fibrin can be collected from blood, and forms gels by the enzymatic polymerization of fibrinogen at room temperature in the presence of thrombin (Ikari et al, 2000). Hydrogels can also be formed from synthetic polymers, such as poly(ethylene glycol), poly(vinyl alcohol), poly(2-hydroxy ethyl methacrylate), and polyethylene glycol (PEG).…”
Section: Patterned Cell Culture Substrates: Fabrication Methods and Matmentioning
confidence: 99%